2021
DOI: 10.1039/d1ob00546d
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric bis(oxazoline)–Ni(ii) catalyzed α-hydroxylation of cyclic β-keto esters under visible light

Abstract: With using the visible light as driving force and the molecular oxygen as green oxidant, we developed bis(oxazolines)-Ni(acac)2 asymmetric catalyzed α-hydroxylation of β-keto esters in the presenceof a low photosensitizer...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Based on the experimental results and the previous studies, 11–14,17 a plausible reaction pathway was suggested. As shown in Scheme 4c, the pre-synthetic ethylenediamine–copper( ii ) complex acting as a Lewis acid catalyst to form the copper enolate species bearing increased nucleophilicity.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Based on the experimental results and the previous studies, 11–14,17 a plausible reaction pathway was suggested. As shown in Scheme 4c, the pre-synthetic ethylenediamine–copper( ii ) complex acting as a Lewis acid catalyst to form the copper enolate species bearing increased nucleophilicity.…”
Section: Resultsmentioning
confidence: 91%
“…At present, considerable achievements have been made in this promising project by Meng's groups using the salan-copper( ii ) and cinchona alkaloid derivatives as a catalyst for activating the β-keto esters and tetraphenyl-porphyrin (TPP) or phthalocyanine (PC) as the optimal photosensitizer. 11 Meanwhile, the combination of bis(oxazoline)–Ni( ii ) complexes and a visible light photosensitizer in grafting or physically mixed way, reported by Xiao's group 12 and our group, 13 respectively, providing alternative catalysis systems to realize this transformation. Despite these important advances, when we consider the long-standing challenges that lowing catalyst and photosensitizer loading, using structurally simple catalyst and achieving excellent catalyst performance and practicable reaction scale-up in such light-mediated oxidative α-hydroxylation of β-dicarbonyl compounds, developing new competent catalytic system to be compatible with photooxidation remain highly desirable (Scheme 1 and Fig.…”
Section: Introductionmentioning
confidence: 99%